The Faces of Estonian Sovietisation: A Look Back. Notes on the publication: Sovietisation and violence: the case of Estonia. 2018. Tartu: University of Tartu Press, ed. Meelis Saueauk, Toomas Hiio. Proceedings of the Estonian Institute of Historical Memory. Eesti Mälu Instituudi toimetised 1 (2018). 335 pp. ISBN 9789949778249. ISSN 2613–5981 - Bułhak, Władysław (Institute of National Remembrance Review, 2021)
This article critically discusses the publication entitled Sovietisation and violence: the case of Estonia, edited by Meelis Saueauk and Toomas Hiio, published in 2018 by the University of Tartu Press as the first volume of the Proceedings of the Estonian Institute of Historical Memory series. The author of this article refers in detail to several of the studies and articles published in the volume, most of which were written by researchers associated with its publisher, the Estonian Institute of Historical Memory. In terms of content, as the reviewer notes, the publication’s aim is to introduce the international academic reader to the topic of the forced Sovietisation of Estonia in the 20th century. The author will attempt to assess to what extent the discussed volume lives up to the hopes placed in it. Overall, he concludes that despite all the errors and omissions noted, the publication’s desired aim was achieved, while also showing the above-named institution’s potential as a scholarly research unit with ambitions reaching beyond the local academic market.